Social Institution in the Six Directions Teaching in Singalaka Sutta - Thangthongmadan, Sathien (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 2 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
This article has two objectives: 1) to study the concept of social institutions in terms of meaning, composition, and type of social institutions; and 2) to study the social institutions that appear in the doctrine of the six directions in the Singalaka Sutta. This is a documentary. The study is found that Social Institution in the doctrine of the six directions in the Singalaka Sutta reflect on four social institutions namely: Family institution, Educational institution, Economic institutions and religious institutions. These institutions are concrete. These are a group of people to achieve a common purpose. These are Abstracts. Each institution has its own rules and regulations. These are an example of shared behavior among members of society. The status and roles are clearly defined. And social institutions are permanent. The society will not decline as long as there are human beings.